Kayu sebagai Bahan Bangunan Bertingkat Tinggi yang Ramah Lingkungan (Timber as Environmentally Friendly High-Rise-Building Materials) - Lestari, Ratri Yuli (Jurnal Riset Industri Hasil Hutan, 2016)
Wood has been widely used as building materials. The trends of using wood as construction materials in a building are keep increasing because the positive trend in construction expertise to use wood as building construction. Wood can be used as building materials such as structural construction, decking, roofing, flooring, cladding, furniture and interior. Wood is chosen because it is easy to work, flexible in design, high energy efficiency, low embodied energy, low global warming potential, fire resistance, and importantly wood is renewable and recyclable resources. Each country has their own regulations related to the application of wood as materials in high rise building. However, these regulations stimulated the expertises to demonstrate that wood is capable to be high-rise building materials and fulfil the safety building requirements.Â Keywords : wood, high-rise building, environmentally friendly